Copper and Zinc Levels in Commercial Marine Fish from Setiu, East Coast of Peninsular Malaysia - Yap, Chee Kong; Al-Mutairi, Khalid Awadh (MDPI, 2022)
Potentially toxic metals (PTMs) in edible marine fish have been widely reported from at least 15 different regions or countries in the literature. This evidently demonstrates the importance of monitoring the PTMs in fish fillets from a human health risk (HHR) point of view. This study aims to assess the HHR of Cu and Zn in 19 species of marine fish from popular marine fish loading sites at Setiu in Terengganu, on the east coast of Peninsular Malaysia, collected between August 2016 and February 2017. With overall ranges of concentrations (mg/kg dry weight) of Cu (1.50–7.83), and Zn (24.1–80.5), the 19 species of marine fishes from Setiu are good sources of these essential elements because they are below the maximum permissible limits set by seafood safety guidelines. The target hazard quotient values of Cu and Zn were lower than one, indicating non-carcinogenic risks of Cu and Zn in fish consumption. It was also found that the calculated values of the estimated weekly intake were below the established provisional tolerable weekly intake of Cu and Zn. It can be concluded that the consumption of fish from Setiu would not pose adverse effects from the PTMs to consumers. Nonetheless, continuous monitoring is necessary to ensure the safety of consumers who rely heavily on marine fish in Setiu coastal waters.